CURRENT STATUS OF THE PATHOGENESIS, CLINICAL FEATURES, DIAGNOSIS, AND TREATMENT - I. S. Sidorova; A. L. Unanyan; M. B. Ageev; N. V. Vedernikova; M. N. Zholobova (Акушерство, гинекология и репродукция)
The article describes the present views on the etiology, pathogenesis and morphogenesis of uterine myoma. The data on the role of steroid hormones and their receptors, growth factors, and processes of proliferation and apoptosis, and also compares the types of growth of uterine myoma according to the histological types of tumor development. Pressing questions organ preservation treatment of uterine myoma in women of reproductive age.